The comparative effects of oral Chinese patent medicines combined with western medicine in stable angina: A systematic review and network meta-analysis of 179 trials - Peiying Huang; Zhishang Li; Li Chen; Jing Zeng; Shuai Zhao; Yong Tang; Bixuan Huang; Hansu Guan; Yan Chen; Yuchao Feng; Sisi Lei; Qihua Wu; et al. (Frontiers Media S.A., 2022)
Background: Stable angina is a common condition with high morbidity and mortality rates. It has been reported that combining oral Chinese patent medicines (OCPMs) and Western medicine (WM) could potentially achieve a better effect than WM alone. However, the optimal OCPMs for stable angina remain controversial and merit further empirical research.Methods: PubMed, Embase, Web of Science, Cochrane Library, Ovid-Medline, Clinical Trials.gov, China National Knowledge Infrastructure, Wanfang Database, Weipu Journal Database, and Chinese Biomedical Literature Database were all searched from inception to 13 March 2022. We employed Version 2 of the Cochrane risk-of-bias tool (ROB2) to assess the overall quality of the selected studies. We also used R 4.1.2 and STATA 14.0 software applications to perform network meta-analysis, followed by sensitivity and subgroup analysis.Results: A total of 179 randomized controlled trials with 16,789 patients were included. The selected trials were all assessed as some concerns. OCPMs combined with WM had a better treatment effect than WM alone. In terms of the effective clinical rate, a significant increase was detected for Qishen Yiqi dripping pill (QSYQ)+WM as compared with Shensong Yangxin capsule (SSYX)+WM, Shexiang Baoxin pill (SXBX)+WM, Tongxinluo capsule (TXL)+WM, Xuefu Zhuyu capsule (XFZY)+WM, Qiliqiangxin capsule (QLQX)+WM, Naoxintong capsule (NXT)+WM, Fufang Danshen dripping pill (FFDS)+WM, and Danlou tablet (DL)+WM. QSYQ + WM had the highest-ranking probability (98.12%). Regarding the effective rate in ECG, QSYQ + WM was superior to SXBX + WM, TXL + WM, DL + WM, FFDS + WM, and NXT + WM. QSYQ + WM ranked first (94.21%). In terms of weekly frequency of angina, QLQX + WM obtained a better effect than FFDS + WM, Kuanxiong aerosol (KXQW)+WM, NXT + WM, QLQX + WM, SSYX + WM, SXBX + WM, and TXL + WM. QLQX + WM ranked first (100.00%). Regarding the duration of an angina attack, KXQW + WM was superior to SSYX + WM; KXQW + WM ranked first (95.71%). Adverting to weekly nitroglycerin usage, TXL + WM had the highest-ranking probability (82.12%). Referring to cardiovascular event rate, DL + WM had the highest effect (73.94%). Additionally, SSYX + WM had the lowest rate of adverse drug reactions (1.14%).Conclusion: OCPMs combined with WM had a higher efficacy. QSYQ + WM, QLQX + WM, KXQW + WM, TXL + WM, DL + WM, SSYX + WM, and SXBX + WM merit further investigation. SXBX + WM is presumably the optimal treatment prescription for both clinically effective and cardiovascular event rates. Further high-quality empirical research is needed to confirm the current results.Systematic Review Registration: URL = https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=316534, CRD 42022316534